2013
DOI: 10.3109/10641963.2013.810235
|View full text |Cite
|
Sign up to set email alerts
|

The impact of metabolic syndrome, recently diagnosed diabetes and hypertension on right ventricular remodeling. Is there difference between risk factors?

Abstract: The aim of this study was to compare the right ventricular (RV) structure and diastolic function between normotensive and non-diabetic subjects with metabolic syndrome (MS), and new diagnosed diabetic and hypertensive patients. Study included 89 normotensive and non-diabetic subjects with MS which was defined by the presence ≥3 ATP-NCEP-III criteria, 45 diabetic and 117 hypertensive patients, as well as 76 controls with no MS criteria, matched for age and sex. All subjects underwent laboratory blood tests and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…We have also demonstrated that similar changes occur with the left ventricular structure and diastolic function in hypertensive patients. This is in line with our previous findings [10,20,21], and the results of other authors [22][23][24][25]. However, our study provided some new evidence about right ventricular function.…”
Section: Discussionsupporting
confidence: 95%
“…We have also demonstrated that similar changes occur with the left ventricular structure and diastolic function in hypertensive patients. This is in line with our previous findings [10,20,21], and the results of other authors [22][23][24][25]. However, our study provided some new evidence about right ventricular function.…”
Section: Discussionsupporting
confidence: 95%
“…However, only RA conduit and booster function were independently Int J Cardiovasc Imaging associated with HbA1c. Interestingly, in our previous study we did not find any difference in RA size between the diabetic patients and the healthy subjects; however, we did not investigate RA volumes [28]. Our investigation revealed that HbA1c, RV wall thickness, E/e 0 t and RA TotEF were independently associated with RA global longitudinal strain, which we reported earlier in the population of patients with high-normal blood pressure and hypertension [29,30].…”
Section: Discussionsupporting
confidence: 39%
“…We have previously demonstrated that RA diameters and maximal volume were higher in hypertensive patients. 11,12,27 Using the 2DE strain analysis, we have recently reported impaired RA reservoir and conduit, and enhanced booster function among the hypertensive subjects. 11,12 However, this is the first time that we conducted a comprehensive analysis of phasic function of both atria in hypertensive subjects, using all available 2DE methods.…”
Section: Discussionmentioning
confidence: 99%